2003
DOI: 10.3748/wjg.v9.i11.2424
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic mechanism of ginkgo biloba exocarp polysaccharides on gastric cancer

Abstract: AIM:To study the therapeutic mechanism of Ginkgo biloba exocarp polysaccharides (GBEP) on gastric cancer. METHODS:Thirty patients with gastric cancer were treated with oral GBEP capsules. The area of tumors was measured by electron gastroscope before and after treatment, then the inhibitory and effective rates were calculated. The ultrastructures of tumor cells were examined by transmissional electron microscope. Cell culture, MTT, flow cytometry were performed to observe proliferation, apoptosis and changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 21 publications
(20 reference statements)
0
21
0
Order By: Relevance
“…Ginkgolide B (GB) is a component of ginkgo leaf, which has been widely used for treating asthma, cough and enuresis [22,23]. Previous studies have shown that GB has beneficial effects on endothelial cell protection [24] as well as cancer therapy [25][26][27]. However, whether GB may have an anti-bladder cancer effect is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Ginkgolide B (GB) is a component of ginkgo leaf, which has been widely used for treating asthma, cough and enuresis [22,23]. Previous studies have shown that GB has beneficial effects on endothelial cell protection [24] as well as cancer therapy [25][26][27]. However, whether GB may have an anti-bladder cancer effect is not known.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies conducted with various molecular, cellular, and whole animal models have revealed that leaf extracts of Ginkgo biloba may have anticancer (chemopreventive) properties that are related to their antioxidant, antiangiogenic, and gene or protein regulatory actions. [6][7][8][9] Cell line studies suggest that Ginkgo may reduce the growth of human breast cancer cells, perhaps through its action on the peripheral-type benzodiazepine pathway that is important in steroid hormone regulation, 10 and it has significant antiproliferative and cytotoxic effects on human hepatocellular carcinoma cells. 11 In vivo experiments suggest that Ginkgo may promote apoptosis of cancer cells by caspase-3/8 activation in oral cancer cells in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional cytotoxic drugs are powerful enough to kill tumor cells, but they come with high toxicity, especially with regards to immune and hemotologic function [30] . Thus, many doctors avoid using these kinds of drugs to their patients.…”
Section: H U M O R a L I M Mu N I T Y I S C R I T I C A L T O H O S Tmentioning
confidence: 99%